La Mediación Familiar previa a iniciar la vía judicial, en materias transigibles de pensiones alimenticias, régimen de visitas y alimentos para mujer embarazada, en cumplimiento al procedimiento alternativo de solución de conflictos - Rueda Sinchire, Maricela Karina (2018)
In the present thesis entitled: "FAMILY MEDIATION, PRIOR TO INITIATING THE JUDICIAL PATH, IN TRANSGENABLE MATTERS OF FOOD PENSIONS, VISIT AND FOOD REGIME FOR PREGNANT WOMEN, IN COMPLIANCE WITH THE ALTERNATIVE PROCEDURE OF CONFLICT RESOLUTION, arises from the study of a current problem, which refers to the congestion of the Judicial Units of the Family, Women, Children and Adolescents, in processes of alimony, visits and food for pregnant women, Problematic that has been verified through the development of this research work through the literature review sections, application of survey and interview techniques, verification of objectives and testing of the hypothesis and also considering that mediation is recognized from the Constitutional scope in Art. 190 that categorizes it as an alternative dispute resolution procedure that must be applied subject to the law in matters that by their nature can be compromised and in the same way article 294 of the Organic Code of Children and Adolescents, establishes that it will be applied in family matters as long as it does not violate inalienable rights of children and adolescents. Postulates that helped me to substantiate the need to propose a proposal for legal reform to the Organic Code of Children and Adolescents, General Organic Code of Process and Law on Arbitration and Mediation, aimed at defining family mediation prior to initiating judicial proceedings in transferable family matters and that therefore the citizenship benefits from a conflict resolution based on a culture of peace and dialogue guaranteeing the effective enjoyment of the rights of the holders of these actions.